PENGENDALIAN KUALITAS LAYANAN JASA PERPUSTAKAAN BERDASARKAN PERSEPSI PENGUNJUNG - Utami, Hadiahti -; Barokah, Siti Nur; Taviyastuti, Taviyastuti - (Admisi dan Bisnis, 2019)
The library has a very meaningful role, especially for universities. With good management, the library will have a positive impact on the users it serves. This study aims to determine the level of disparity between service quality perceived by visitors to the services provided by the library management, determine the level of visitor satisfaction with the facilities provided, and find out the quality of Semarang State Polytechnic Library service is still within the control limits. Primary data collection is done through a survey with a closed questionnaire tool obtained from 100 respondents who visited Semarang State Polytechnic Library. The results of research conducted based on the Importance-Performance Analysis show that there are still variables that have below-average performance levels but are of high importance, based on the analysis of the Customer Satisfaction Index (CSI), Library visitor satisfaction index Semarang State Polytechnic as a whole has succeeded in satisfying its visitors by 75.715%, and based on individual control diagrams in the sample indicate that performance variations are not within the limits reasonable (the process is not statistically controlled). Thus the performance of the Semarang State Polytechnic Library Service Quality still needs to be improved and improved.